Hubungan Klorofil-a dan Suhu Permukaan Laut (SPL) Terhadap Hasil Tangkapan Ikan Lemuru Sardinella lemuru di Selat Bali Menggunakan Citra Aqua MODIS Tahun 2009-2018 - Clinton, Rony; Gede Astawa Karang, I Wayan; Widiastuti, Widiastuti (Journal of Marine Research and Technology, 2022)
Oceanographic parameters such as sea surface temperature (SST) and chlorophyll-a in the water can influence the productivity of pelagic fish such as Lemuru. Many studies have been conducted on the relationship between SST and chlorophyll-a and the fluctuations in the catch of Lemuru fish, especially using satellite databased sensing technology. Most of the research using satellite data is done in a short-term period (not climatology), so there are still a lot of unanswered questions. One of them is: how the correlation between the fluctuation in the number of Lemuru fish catches is related to SST and chlorophyll-a in the ENSO and IOD periods. The purpose of this study is to determine the distribution of SST and chlorophyll-a concentrations and their relationship with the yield of Lemuru fish catches in the Bali Strait from 2009 to 2018. Aqua Moderate Imaging Spectroradiometer (MODIS) satellite data level 2 from Oceancolor and data on the number of fish caught in the Bali Strait from the National Fisheries Port (PPN) Pengambengan and UPT PPP Muncar. The method is used with correlation analysis between SST and chlorophyll-a to the number of Lemuru fish caught. The monthly average SST in Bali Strait waters from 2009 to 2018 was approximately 24,76 0 C-30, 11 0 C, with an estimated monthly chlorophyll-a concentration of 0,10 mg/m 3 -3,68 mg/m 3 . The spatial distribution of SST tends to be low in the southern Bali Strait and tends to be high in the northern Bali Strait. The spatial distribution of chlorophyll-a appears to have a high value in the near land area. The cross-correlation test between chlorophyll-a and the number of Lemuru catches showed a positive correlation yield at the 4th month lag. While the correlation of SST to the number of Lemuru fish catches shows a positive correlation at lag (-1).